Pengaruh Norma Subjektif, Kesadaran Wajib Pajak, Kualitas Pelayanan dan Sanksi Perpajakan Terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor di Samsat Kabupaten Pemalang - Dhalifah Nur Rohmah (Faculty of Economics and Business, University of Pancasakti Tegal, 2018)
This study aims to determine the Influence of Subjective Norms, Taxpayer Awareness, Service Quality and Tax Sanctions on Compliance of Motorized Taxpayers on SAMSAT Pemalang District. This study uses primary data obtained from respondents' answers to the questionnaires used in the study. Data analysis method uses Descriptive Statistics, Testing Instrument Research, Classical Assumption Test, Multiple Regression Analysis, Hypothesis Test and Determination Coefficient. Research results show that the F test of subjective norm variables, taxpayer awareness, service quality and tax sanctions affect simultaneously on motor vehicle taxpayer compliance in SAMSAT Pemalang District. Partially, the Subjective Norm variable does not significantly influence the Motor Vehicle Taxpayer Compliance variable, the variable of Taxpayer Awareness has a significant influence on Motor Vehicle Taxpayer Compliance, Service Quality variable has a significant effect on Motor Vehicle Taxpayer Compliance, Tax Sanction variable does not significantly influence Motor Vehicle Taxpayer Compliance.